Prospective validation of candidate SNPs of VEGF/VEGFR pathway in metastatic colorectal cancer patients treated with first-line FOLFIRI plus bevacizumab. - Fotios Loupakis; Chiara Cremolini; Dongyun Yang; Lisa Salvatore; Wu Zhang; Takeru Wakatsuki; Pierre Bohanes; Marta Schirripa; Leonor Benhaim; Sara Lonardi; Carlotta Antoniotti; Giuseppe Aprile; et al. (PLoS ONE, 2013)
The potential impact of different SNPs of VEGF/VEGFR pathway on the clinical outcome of mCRC patients receiving bev-containing regimens has been investigated in retrospective experiences with contrasting results. We previously reported the association of VEGFA rs833061 C/T variants with PFS in metastatic colorectal cancer patients treated with first-line FOLFIRI plus bevacizumab. The primary objective of this work was to prospectively validate that retrospective finding. A confirmatory analysis of other SNPs of VEGF/VEGFR pathway genes was included.To detect a HR for PFS of 1.7 for VEGFA rs833061 T/T compared to C- variants in metastatic colorectal cancer patients treated with first-line FOLFIRI plus bevacizumab, setting two-sided α = 0.05 and β = 0.20, 199 events were required. VEGFA rs699946 A/G, rs699947 A/C, VEGFR1 rs9582036 A/C and rs7993418 A/G, VEGFR2 rs11133360 C/T, rs12505758 C/T and rs2305948 C/T and EPAS1 rs4145836 A/G were also tested. Germ-line DNA was extracted from peripheral blood. SNPs were analyzed by PCR and sequencing.Four-hundred-twenty-four pts were included. At the univariate analysis, no differences according to VEGFA rs833061 C/T variants were observed in PFS (p = 0.38) or OS (p = 0.95). Among analyzed SNPs, only VEGFR2 rs12505758 C- variants, compared to T/T, were associated to shorter PFS (HR: 1.36 [1.05-1.75], p = 0.015, dominant genetic model) and OS, with a trend toward significance (HR: 1.34 [0.95-1.88], p = 0.088). In the multivariate model, this association retained significance (HR: 1.405 [1.082-1.825], p = 0.012) in PFS, that was lost by applying multiple testing correction (p = 0.14).This prospective experience failed to validate the hypothesized predictive impact of VEGFA rs833061 variants. Retrospective findings on different candidate SNPs were not confirmed. Only VEGFR2 rs12505758 variants, whose prognostic and not predictive impact was previously reported, correlated with PFS. Given the complexity of angiogenesis, it is rather unlike that a single germ-line SNP might be a good predictor of benefit from bevacizumab.